Monetary and Exchange Rate Policies of the Euro Area : Selected Issues. (IMF Staff Country Reports; Country Report, 2002)
This paper examines monetary and exchange rate policies of the euro area. The paper reviews the European Central Bank's definition of price stability, and examines the factors determining 'the optimal rate of inflation' in the euro area. It reviews the benefits of price stability, including the reduction in the distortions of savings and investment behavior that stem from the interaction between nominal tax systems and inflation. It then goes on to evaluate arguments for maintaining a small positive inflation rate in the context of the euro area.